Intravenous administration of sodium propionate induces antidepressant or prodepressant effect in a dose dependent manner - Hao, Chunyan (Sci Rep, 2020)
Propionate has been reported to exert antidepressant effects, but high-dose propionate may induce autism-like symptoms in experimental animals through induction of dysbiosis of neurotransmitters. The bi-directional effects of propionate seem to be dose-dependent. However, due to the pathological discrepancies between depression and autism, conclusions drawn from autism may not be simply transferable to depression. The effect and underlying action mechanisms of high-dose propionate on depression remains undetermined. To investigate the effects of propionate on depression, propionate dose gradients were intravenously administrated to rats exposed to chronic unpredictable mild stress (CUMS) for 1 week. Results of these behavioral tests demonstrate that low-dose propionate (2 mg/kg body weight/day) induces antidepressant effect through bodyweight recovery, elevated reward-seeking behaviors, and reduced depression-like behaviors, while high-dose propionate (200 mg/kg body weight/day) induces prodepressant effects opposite of those of low-dose propionate. A comprehensive profiling of neurotransmitters in the hippocampus demonstrated that CUMS induces reduction of NE (Norepinephrine), DA (Dopamine). GABA (γ-aminobutyric acid) was recovered by low-dose propionate, while high-dose propionate exerted more complicated effects on neurotransmitters, including reduction of NE, DA, 5-Hydroxytryptamine and Tryptophan, and increase of GABA, Kynurenine, Homovanillic acid, 3-hydroxyanthranilic acid, 3-hydroxykynurenine, 3,4-dihydroxyphenylacetic acid, and 3-methoxytyramine. The neurotransmitters disturbed by high-dose propionate suggest metabolic disorders in the hippocampus, which were confirmed by the clear group separation in PCA of metabolomic profiling. The results of this study demonstrate the double-edged dose-dependent effects of propionate on depression and suggest potential cumulative toxicity of propionate as a food additive to mood disorders.